2008
DOI: 10.1037/0735-7036.122.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Memory for individuals: Hamsters (Mesocricetus auratus) require contact to develop multicomponent representations (concepts) of others.

Abstract: In humans, individuals recognize other individuals by numerous types of independent information, such as the quality of the voice, appearance of the face, smell, gait, and posture. Humans also have integrated memories of others--that is, in response to a face or a voice the individual is recognized by name and other information about that individual is remembered. In many nonhuman species, individual recognition also occurs. Although observational studies suggest that individuals of some nonhuman species may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 76 publications
1
25
0
Order By: Relevance
“…Nonhuman primates can process audiovisual information cross-modally to match indexical cues (20) and number of vocalizers (21), to match and tally quantity across senses (22) and associate the sound of different call types with images of conspecifics and heterospecifics producing these calls (23)(24)(25). Research aimed specifically at investigating the categorization of individuals has shown that hamsters (Mesocricetus auratus) are capable of matching multiple scent cues to the same individual (26) and that certain highly enculturated chimps (Pan troglodytes) can, through intensive training, learn to associate calls from known individuals with images of those individuals (27)(28)(29). Some species have also been shown to spontaneously integrate auditory and visual identity cues from their one highly familiar human caretaker during interspecific, lab-based trials (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Nonhuman primates can process audiovisual information cross-modally to match indexical cues (20) and number of vocalizers (21), to match and tally quantity across senses (22) and associate the sound of different call types with images of conspecifics and heterospecifics producing these calls (23)(24)(25). Research aimed specifically at investigating the categorization of individuals has shown that hamsters (Mesocricetus auratus) are capable of matching multiple scent cues to the same individual (26) and that certain highly enculturated chimps (Pan troglodytes) can, through intensive training, learn to associate calls from known individuals with images of those individuals (27)(28)(29). Some species have also been shown to spontaneously integrate auditory and visual identity cues from their one highly familiar human caretaker during interspecific, lab-based trials (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Hamsters, they suggest, have an integrated, multiodor memory of other individuals. Recent experiments indicate that direct physical contact with an individual-not just exposure to its odors-is necessary for such memories to develop (12).…”
Section: Individual Recognitionmentioning
confidence: 99%
“…However, while individual recognition is thought to be a widespread ability [3], providing robust scientific support for recognition at the level of the individual has proved difficult [4,5]. 'True' individual recognition strictly constitutes the identification of a specific individual, according to individually distinct cues, and the placement of that individual within a society of many others [6].…”
Section: Introductionmentioning
confidence: 99%